Australia's medical innovation approach: is it suitable for regenerative medicine? - Gardner, J; Morrison, M (Open Access Government, 2021)
Australia has committed to investing heavily in its medical future – but will it be ready for the regenerative medicine revolution? John Gardner from Monash University and Michael Morrison from the University of Oxford provide the answer.